The Influence of Interpersonal Communication on Employee Performance at the Department of Industry and Trade of Gowa Regency - Achmad Fathanah Tarman; Dg. Maklassa; Nurinaya (www.amertainstitute.com, 2025)
This study aims to determine the influence of interpersonal communication on employee performance at the Department of Industry and Trade of Gowa Regency. Interpersonal communication is an essential element in creating a productive and harmonious work environment, directly impacting employee performance. This study applied a quantitative approach using a descriptive method. The sample consisted of 37 employees selected using a saturated sampling technique. Data were collected using questionnaire and analyzed using simple linear regression. The results showed that interpersonal communication has a positive and significant effect on employee performance, as indicated by a significance value of 0.001 (< 0.05) and a determination coefficient of 0.285. This means that interpersonal communication explains 28.5% of the variation in employee performance. The findings emphasize the importance of strengthening interpersonal communication as a strategic effort to improve the performance of government institution employees.